MENINGKAKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING: IMPROVING MOTIVATION AND LEARNING OUTCOMES IN MATHEMATICS THROUGH THE APPLICATION OF A CONTEXTUAL TEACHING AND LEARNING APPROACH - Layn, Ruslan; Setyo, Arie Anang; Musa'ad, Faida; Gegetu, Usman (Universitas Muhammadiyah Sorong, 2024)
This study uses a contextual teaching and learning (CTL) strategy to enhance students' mathematical learning outcomes and motivation when studying flat-sided geometric material. There are four phases to the implementation of this classroom action research approach: planning, carrying out the action, observing, and reflecting. Thirty pupils in the VIII B MT class. In this study, Al-Akbar Sorong City is the focus. According to the research findings, student learning outcomes in Cycle I had an average score of 67.00, placing them in the